Novel HCN1 Mutations Associated With Epilepsy and Impacts on Neuronal Excitability - Xie, Changning; Liu, Fangyun; He, Hailan; He, Fang; Mao, Leilei; Wang, Xiaole; Yin, Fei; Peng, Jing (Frontiers in Molecular Neuroscience, 2022)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channel plays a critical role in regulating the resting membrane potential and integrating synaptic transmission. Variants of HCN1 have been recognized as causes of epilepsy, and mutant HCN1 channels could act with loss-of-function (LOF), loss- and gain-of-function (LOF and GOF) and gain-of-function (GOF) mechanisms. However, phenotypes and pathogenesis of HCN1-related epilepsy are still poorly understood. This study enrolled five epileptic cases carrying five different HCN1 variants: two pathogenic variants (I380F and S710Rfs*71), two likely pathogenic variants (E240G and A395G), and a paternally inherited variant (V572A). Four variants were novel. Electrophysiological experiments revealed impaired biophysical properties of the identified mutants, including current densities and activation/deactivation kinetics. Moreover, three variants exerted effects on the biophysical properties of wild-type HCN1 channels in heterozygous conditions. Immunofluorescence experiments showed that two variants reduced the protein expression of HCN1channels in neurons. Neurons expressing E240G (GOF) variant showed increased input resistance. However, the variant of I380F (LOF) increased the neuronal firing rate, thus leading to neuronal hyperexcitability. In conclusion, the present study expands the genotypic and phenotypic spectrum of patients with HCN1-related epilepsy and clarifies the underlying mechanisms. We reported five new cases including four unreported likely/pathogenic variants. We provided assessments of biophysical function for each variant, which could help patients to receive individual therapy in the future. We confirmed that HCN1 variants contributed to neuronal hyperexcitability by regulating input resistance and the action potential firing rate, and we have shown that they can affect protein expression in neurons for the first time.